Proceedings of the 6th Nordic Conference on Human-Computer Interaction: Extending Boundaries 2010
DOI: 10.1145/1868914.1868972
|View full text |Cite
|
Sign up to set email alerts
|

Eyes-free text entry with error correction on touchscreen mobile devices

Abstract: We present an eyes-free text entry method for mobile touchscreen devices. Input progresses by inking Graffiti strokes using a finger on a touchscreen. The system includes a word-level error correction algorithm. Auditory and tactile feedback guide eyes-free entry using speech and non-speech sounds, and by vibrations. In a study with 12 participants, three different feedback modes were tested. Entry speed, accuracy, and algorithm performance were compared between the three feedback modes. An overall entry speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition to tap typing, some research investigated gesturebased text entry on touchscreen, such as an eyes-free Graffiti text input system [23,25] and a swipe-based invisible text entry method with numberpad-like layout on smartwatches [17].…”
Section: Eyes-free Text Entrymentioning
confidence: 99%
“…In addition to tap typing, some research investigated gesturebased text entry on touchscreen, such as an eyes-free Graffiti text input system [23,25] and a swipe-based invisible text entry method with numberpad-like layout on smartwatches [17].…”
Section: Eyes-free Text Entrymentioning
confidence: 99%
“…While the visual layout of the QWERTY keyboard is identical to that presented to sighted users, the text-entry rates are much slower for visually impaired users [19]. To address this problem a number of works have proposed novel interfaces for non-visual text-entry on mobile touchscreen devices; including new keyboard layouts [3,8] and alternative methods of inputting text [1,16,19,22,23].…”
Section: Text Input For Blind Usersmentioning
confidence: 99%
“…Text entry can also be implemented using ad i ff erent touch screen gesture for each character.T inwala and MacKenzie [24] used gestures that resemble letters as input and auditory and tactile feedback to guide eyes-free entry.Letters were entered one at atime and word-levelerror recognition with adictionary wasused to improve accuracy. Tinwala and MacKenzie suggested that changing the speech feedback from the character-leveltothe wordlevels peeds up writing and lessens user frustration.…”
Section: Assistive Technologymentioning
confidence: 99%